Los juegos grupales para el desarrollo del ámbito de convivencia en los niños de inicial 2 de la Unidad Educativa “Simón Rodríguez” de la ciudad de Riobamba, provincia de Chimborazo. - Morocho Cuvi, Doris Vanessa (2023)
The present research work focuses on “TEAM GAMES FOR THE ENVIRONMENTAL DEVELOPMENT OF COEXISTENCE IN CHILDREN OF 2ND. EARLY EDUCATION AT THE EDUCATIONAL UNIT "SIMÓN RODRÍGUEZ". In Riobamba town, province of Chimborazo, the aim is to analyze the influence of team games in the environmental development of coexistence. Regarding the foundation terms related to the study are categorized in order to gives the theoretical framework the importance of the problem- solving. The study attempts to discuss traditional teaching methods and the social impact that arises from their practice. Qualitative research focuses on hermeneutics, which describes the results obtained through data collection, techniques and instruments, such as, qualitative and the observation sheet. The key informants for the application instruments comprised 30 students of the early childhood Education . After interpreting the data, it is estimated that one of the most relevant results of this study, the students "Always" develop camaraderie and mutual support among their classmates.